Unesp e Ditadura Militar: tragédia e farsa - Caldas Júnior, Antonio Luiz [UNESP] (My University, 2014)
The 1964 coup, more precisely designated as civilian-military, was supported by Brazilian citizens, including universities, and had serious consequences due to its authoritarian, arbitrary and repressive character. We should remember it lest it never be reinvented. This article examines the relationship between Unesp and the dictatorship, from 1976 to 1985, with author memories and literature review. The foundation of Unesp, a few shining examples of arbitrary authoritarianism at universities, among which police invasion and strikes, the relationship with dictatorial power, and the struggle for democratization, such as the Rector’s succession in 1984, are mentioned. It is concluded that the acts of the dictatorship, albeit repudiated by most Brazilians, spread its tentacles to Unesp, its central leaders and most of its Schools and Institutes, in the form of authoritarianism, typical of oligarchy. It was found that, although Brazilian society moved towards democracy, shown by the election of democrats at state level, Unesp’s leaders managed it in an increasingly authoritarian and unbounded fashion. If the dictatorship was a tragedy, it was repeated at Unesp with shades of farce.

O Golpe de 1964, melhor tratado como Civil-Militar, contou com apoio de setores civis da sociedade brasileira, inclusive nas universidades, com graves consequências decorrentes de seu caráter autoritário, arbitrário e repressivo, sendo necessário rememorá-lo para que nunca seja reinventado. O objetivo deste artigo é contribuir para o conhecimento das relações Unesp - Ditadura Civil-Militar, de 1976 a 1985, por meio de memórias do autor e revisão da literatura. São abordados a criação da Unesp, alguns episódios emblemáticos do autoritarismo arbitrário na vida universitária, incluindo invasões policiais e greves, as relações com o poder ditatorial e as lutas pela democratização, como por ocasião da sucessão do Reitor, em 1984. Conclui-se que as ações da Ditadura, embora repudiadas pela maioria da sociedade brasileira, encontraram abrigo na Unesp, pelas mãos de seus dirigentes centrais e da maioria das unidades universitárias, sob a forma de sinergismo autoritário, próprio do poder oligárquico. Constatou-se que, enquanto a sociedade brasileira caminhava rumo à democracia, inclusive com a eleição de democratas em governos estaduais, os dirigentes da Unesp a conduziam com acirramento de atos autoritários e discricionários. Se a Ditadura foi uma tragédia, na Unesp essa foi repetida com os tons de farsa.
Unesp and Military Dictatorship: tragedy and farce
Keywords: Brazilian civilian-military dictatorship; 1964 coup; Unesp; Authoritarianism; Ditadura civil-militar brasileira; Golpe de 1964; Unesp; Autoritarismo